Design and Development of MY 2nd EYE for Visually Impaired Person - Anuar , Mohamed Kassim (2011)
This paper discussed on design and development of electronic device by using warning system for visually impaired person usage which is called ‘MY 2 nd EYE’. This electronic device is designed to support and help the visually impaired person around this world to have their own confident in order to travel from one place to another place. This project is about developing of warning system by using a vibration motor as a warning device via microcontroller that received input from distance measurement sensor when detecting obstacle. The vibration motor is a best solution to warn the blind person because it uses touch sense of human when the system is run. In this system, there are four pieces of vibration motor are mounted to the gloves at different locations. Each location will have its own function that show different direction such as front, left, right and down. In this project, the effectiveness of the system gives command the direction of obstacle existence is very important and have been confirmed through simulation and experiment.